2018
DOI: 10.1097/cad.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 promotes migration and invasion of non-small-cell lung cancer by targeting miR-206 and activating Akt/mTOR signaling

Abstract: Long noncoding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) functions as a crucial regulator of metastasis in lung cancer. The aim of this study is to unravel the underlying mechanisms of lncRNA MALAT1 in non-small-cell lung cancer (NSCLC). A cohort of 36 NSCLC tumor tissues and adjacent normal tissues was collected postoperatively from patients with NSCLC. qRT-PCR was performed to detect the expression of MALAT1 in both NSCLC tissues and cell lines. Cell migration and invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 28 publications
2
54
0
Order By: Relevance
“…But as to one LncRNA, the molecular mechanism may contain many aspects. For example, LncRNA‐MALAT1, which is highly conserved among mammals, could not only competitively bind with miR‐145‐5p, miR‐204 and miR‐206 as a ceRNA, but also activate Akt/mTOR signalling pathway in order to induce the metastasis of NSCLC . The same LncRNA may have different molecular mechanism in diverse tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But as to one LncRNA, the molecular mechanism may contain many aspects. For example, LncRNA‐MALAT1, which is highly conserved among mammals, could not only competitively bind with miR‐145‐5p, miR‐204 and miR‐206 as a ceRNA, but also activate Akt/mTOR signalling pathway in order to induce the metastasis of NSCLC . The same LncRNA may have different molecular mechanism in diverse tumours.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LncRNA-MALAT1, which is highly conserved among mammals, could not only competitively bind with miR-145-5p, 121 miR-204 122 and miR-206 123 as a ceRNA, but also activate Akt/mTOR signalling pathway in order to induce the metastasis of NSCLC. 123 The same LncRNA may have different molecular mechanism in diverse tumours. But until now, the studies in LncRNAs are only at the experimental level.…”
Section: Influence the Properties Of Cancer Stem Cell (Csc)mentioning
confidence: 99%
“…In recent years, more and more evidences have shown that miRNA plays a key regulatory role in tumorigenesis and development . For instance, miRNAs are found to affect cell differentiation, proliferation, and apoptosis by reducing the stability of target genes or inhibiting their translation . Exploring the relationship between miRNAs and BC formation provides a new way to define the pathogenic factors of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in these epigenetic factors result in the dysregulation of key oncogenes and tumor suppressor genes [18,19]. Many of the epigenetic events in lung cancer affect cancer hallmarks, such as proliferation [20][21][22][23], invasion [24][25][26], metastasis [27][28][29][30][31][32][33], apoptosis [34][35][36][37], and cell cycle regulation. In addition to cancer hallmarks, several important signaling pathways are affected by epigenetic deregulation in lung cancer, such as the ERK family, the NF-kB signaling pathway, and the Hedgehog signaling pathway [18].…”
Section: Epigenetic Landscape In Lungmentioning
confidence: 99%